2007
DOI: 10.1188/07.cjon.865-872
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Prostate Cancer Morbidity and Mortality in African American Men: Issues and Challenges

Abstract: Prostate cancer is the most commonly diagnosed cancer in men in the United States. It disproportionately affects African American men when compared to other ethnic groups. African American men are two to three times more likely to die of prostate cancer than white men. The reasons for the disparity remain unclear, but several factors may be involved, such as age, race, nationality, nutrition, exercise, and family history of cancer. Detection of prostate cancer in high-risk African Americans is important but co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 57 publications
(51 reference statements)
0
21
1
Order By: Relevance
“…3941 Acculturation was not found to be directly correlated with PCa screening, contrary to other cancer screening studies among Chinese Americans. 4042 We did, however, find that acculturation was significantly correlated with the predisposing, enabling, and health care satisfaction factors. These findings indicate that cultural alignment may be indirectly related to those factors that influence a Chinese American man’s decision to undergo PCa screening.…”
Section: Discussioncontrasting
confidence: 65%
“…3941 Acculturation was not found to be directly correlated with PCa screening, contrary to other cancer screening studies among Chinese Americans. 4042 We did, however, find that acculturation was significantly correlated with the predisposing, enabling, and health care satisfaction factors. These findings indicate that cultural alignment may be indirectly related to those factors that influence a Chinese American man’s decision to undergo PCa screening.…”
Section: Discussioncontrasting
confidence: 65%
“…In addition to obesity, dietary factors have been shown to correlate with PCa initiation and progression, with increased animal fat, cooked red meat and dairy consumption being the most studied dietary risk factors [83–84]. It was reported that African Americans tend to maintain high-fat diets more often than any other racial groups [12], thus possibly facilitating the disparity in PCa initiation, progression and survival. Extensive research aimed to explore the role of dietary patterns in overall PCa risk and its relation to disparity is currently ongoing.…”
Section: Disparities In Survival and The Quality Of Lifementioning
confidence: 99%
“…Thus, the goal of eliminating racial disparities in cancer cannot be achieved without coordinated and sustained efforts to provide high quality prevention, screening, and treatment to all segments of the population, including minorities. In addition, as emphasized by Jones et al [12], additional bio-behavioral studies are required to help identify interventions that will narrow the PCa gap between African Americans and Caucasians.…”
Section: Introductionmentioning
confidence: 99%
“…Involving minorities is particularly important in research on prostate cancer, which affects African American men more than other ethnic groups (Jones, Underwood, & Rivers, 2007). The incidence rate of prostate cancer in African American men is 239.8 per 100,000 compared to 153 per 100,000 for White men, 133.4 per 100,000 for Hispanic men, 91.1 per 100,000 for Asian/Pacific Islander men, and 76.1 per 100,000 for American Indian/Alaska Native men (Horner et al, 2008).…”
mentioning
confidence: 99%